Microwave Cavities for High Performance Double Resonance Atomic Clocks and Sensors - (:unkn) unknown (My University, 2025)
The focus of the research proposed in this project is on microwave cavities and their application in compact high performance vapor cell atomic clocks. Thanks to laser diodes, the laser manipulation of atoms and the advent of optical combs, the field of frequency standards has experienced an impressive evolution in which performances (stability and accuracy) are being pushed to unprecedented limits while maintaining reasonable volume, weight, consumption and complexity. In the case of vapor cell standards (traditionally referred to as “Rubidium clocks”), which are extensively used in frequency metrology, telecommunications and satellite navigation systems, there is a strong interest in improving their frequency stability below the limit of current commercially available devices. The general objective of this project consists in achieving the performances of more complicated standards, but with a significantly smaller volume and consumption.
Keywords: frequency standards; atomic clocks; microwave cavities